Use of Cardiovascular Drugs for Primary and Secondary Prevention of Cardiovascular Disease Among Rural-Dwelling Older Chinese Adults - Cong, Lin; Ren, Yifei; Hou, Tingting; Han, Xiaolei; Dong, Yi; Wang, Yongxiang; Zhang, Qinghua; Liu, Rui; Xu, Shan; Wang, Lidan; Du, Yifeng; Qiu, Chengxuan (Frontiers in Pharmacology, 2020)
Cardiovascular risk factors and related disorders are common among older adults, and use of various classes of cardiovascular (CV) drugs could reduce the risk of cardiovascular disease (CVD). However, data are sparse with regard to the use of CV drugs among rural-dwelling older adults in China. Therefore, this population-based study aimed to describe use of CV drugs among older adults living in the rural communities in China, while taking into account the use of CV drugs for primary and secondary prevention of CVDs. This study included 5,246 participants (age ≥65 years; 57.17% women; 40.68% illiteracy) in the baseline examination of the MIND-China study. In March-September 2018, data on health-related factors, CVDs (ischemic heart disease, atrial fibrillation, heart failure, and stroke), and CV drug use were collected via face-to-face survey, clinical examination, and laboratory tests. We classified CV drugs according to the Anatomical Therapeutic Chemical classification system for western medications and specific cardiovascular effects for the products of traditional Chinese medicine (TCM). We conducted descriptive analysis. The overall prevalence of major cardiovascular risk factors ranged from 14.30% in diabetes and 23.81% in dyslipidemia to 66.70% in hypertension, and CVDs affected 35.07% of all participants (36.28% in women vs. 33.47% in men, p = 0.035). In the total sample, calcium channel blockers (C08) were most commonly used (10.39%), followed by TCM products (7.64%), hypoglycemic agents (A10, 4.73%), renin-angiotensin system (RAS)-acting agents (C09, 4.61%), and lipid-lowering agents (C10, 4.17%). The proportions of CV drugs for primary prevention (i.e., use of CV drugs among people without CVD) were 3.14% for antithrombotic agents (mainly aspirin), 1.38% for lipid-lowering agents, and 3.11% for RAS-acting agents; the corresponding figures for secondary prevention (i.e., use of CV drugs among people with CVD) were 13.97%, 9.35%, and 7.39%. In conclusion, despite highly prevalent cardiovascular risk factors and CVDs, a fairly low proportion of the rural-dwelling older adults take CV medications for primary and secondary prevention. Notably, TCM products are among the most commonly used CV drugs. These results call for additional efforts to promote implementation of the evidence-based recommendations for prevention of CVDs in the primary care settings.